The impact of simulation on the development of critical thinking and reflection among nursing and medical students: a systematic review - Sana Loubbairi; Laila Lahlou; Abdelkader Amechghal; Hicham Nassik (Korean Journal of Medical Education)
Simulation is an educational approach that promotes the mastery of technical skills while advancing the development of non-technical competencies, both of which are widely acknowledged as essential in clinical practice. This review aimed to synthesize findings on the impact of simulation in enhancing critical thinking and reflection among nursing and medical students. Following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), a systematic review was conducted by searching the following databases: PubMed, Science Direct, and Scopus. The quality of the included studies was assessed using Joanna Briggs Institute critical appraisal tools. The protocol was previously registered in the PROSPERO registry (CRD42022371971). From 1,323 studies identified in primary research, 16 were included in this review, involving a total of 1,283 students. Of the 16 studies, seven investigated the impact of simulation on critical thinking and reported a positive effect compared to traditional teaching methods. For student reflection, only one study addressed this theme and reported a positive effect on nursing students. This review demonstrated that simulation has a positive impact on critical thinking; however, its impact on reflection remains inconclusive. Further research is essential to explore its effects across diverse populations, including those in developing countries, to maximize its educational potential in health professions education.